P300 characterization in attentional processing among dyslexic children : An event related potential (ERP) preliminary study - Siti Atiyah, Ali; Tahamina, Begum; Nor Asyikin, Fadzil; Faiz, Mustafar; Faraj, Al-Marri; Faruque, Reza (Elsevier Inc., 2019)
Dyslexia is a language-based learning disability and it is mainly speculated to be caused by the impairment of the visual and auditory processing in maintaining the attention towards the stimulation given. Limited studies in P300 characterization in measuring the attentional processing among dyslexic children. We studied the attentional neural-processing of subjects towards congruence and incongruence of visual and auditory stimulations (modified paradigm) on primary school age dyslexic children compared to non-dyslexics using Event-Related Potential (ERP) test. A total of 8 subjects (4 dyslexics and 4 non-dyslexics) were recruited in this preliminary study. An ERP test was conducted by using 128-sensor net and 19 electrode channels were analysed. A modified paradigm of congruence and incongruence auditory and visual stimulus was used during ERP study and the subjects need to give responds to both stimuli. The value of the mean differences between the congruence and incongruence were analysed using 10-20 electrode system, at 19 different channels, specifically on P300 ERP component. The mean differences of P300 amplitudes and latencies between dyslexics and non-dyslexics subjects were compared using Independent T-Test. There was no significant different of P300 amplitudes across all 19 channels, but most of the channels showed high tendencies of high P300 amplitudes among dyslexics (16 out of 19) and prolong P300 latencies at (11 out of 19 channels). These preliminaries results suggested that the dyslexics exerts more attentional efforts towards the sensory stimulations given compared to non-dyslexics group, with them showed slowed processing speed in processing the target stimulations.